Change Process of Two Postsecondary Teachers in the Early Adoption of an Active Learning Classroom - Fournier St-Laurent, Samuel; Poellhuber, Bruno (Frontiers in ICT, 2018)
There is a growing interest for specialized classrooms, termed active learning classrooms (ALC), which are designed to facilitate the use of active learning methods and information and communication technologies (ICT) by students. Thanks to pioneering studies such as SCALE-UP, there is a better understanding of the benefits of these classrooms and the pedagogy taking place in them. Teachers accustomed to traditional classes have to change many aspects of their pedagogy in order to reap the benefits of the ALCs, however. The purpose of this research is to gain a better understanding of the adoption process of an ALC by teachers and how its adoption modify teaching preferences and practices. Relying on an in-depth case study methodology founded on interviews and questionnaires about the adoption of innovations (CBAM), Approaches to Teaching Inventory, technopedagogical competencies and collaborative, competitive or individual teaching preferences, this article describes the cases of two teachers who used an ALC over a three-semester period. The results show that the teachers develop their courses quickly, with an emphasis on the active learning aspects of their pedagogy rather than on ICT integration, and that there are a lot of personal and management concerns. When the pedagogical changes are stabilized, the teachers retained their personal concerns about the innovation and were highly motivated to collaborate with other ALC users. Finally, apparently minor increases in student-centred teaching approaches result in significant pedagogical changes when they are studied qualitatively. These changes did not lead to a reduction in teacher-centred teaching approaches, suggesting that a significant portion of teacher-directed activities remain.